Biotechnologically Important Enzyme Producing Indigenous Bacteria Isolated from Fruit and Vegetable Wastes Samples Collected from different Local Markets - Sharma, Probir Kumar; Jui, Zakya Sultana; Khan, Tahsin; Islam, Tahmina; Saha, Mihir Lal (Plant Tissue Culture and Biotechnology, 2022)
Enzyme from bacterial sources is much stable and obtained cheaply. Amylases and proteases are among the most important enzymes. During this study, indigenous amylase and protease producing bacteria were isolated from common decayed fruits and vegetable wastes viz. Papaya, Brinjal, Cucumber, Potato and Snake Gourd. Bacterial load ranged in between 0.67 × 109 and 9.06 × 109 cfu/g on NA and 1.50 × 109 and 7.00 × 109 cfu/g on PYG agar medium. Maximum mean bacterial load on both NA (6.19 ± 2.60 × 109 cfu/g) and PYG agar (4.54 ± 1.03 × 109 cfu/g) were observed in decayed papaya. A total of 113 bacterial isolates were primarily isolated. Considering better amylase and protease activity 16 isolates were selected for detailed study. The starch hydrolysis ratio (SHR) of the isolates ranged in between 1.25 ± 0.37 and 2.47 ± 0.23 while casein hydrolysis ratio (CHR) ranged in between 2.35 ± 0.12 and 6.44 ± 1.16. The highest SHR was 2.47 ± 0.23 found in Bacillus sp. of snake gourd and the highest CHR was 6.44 ± 1.16 found in Bacillus subtilis also from snake gourd. Out of the 16 isolates 13 were Gram positive and 3 were Gram negative. Gram positive isolates were identified as Bacillus acidocaldarius (4), B. firmus (2), B. lentus (4), B. subtilis (2) and B. alcalophilus (1). Gram negative isolates were identified as Edwardsiella hoshinae, Proteus myxofaciens and P. mirabilis. Six isolates having higher SHR and CHR were authenticated through molecular identification and were identified as Chryseobacterium sp. S29.2, Bacillus sp. X8, Bacillus sp. strain GA1B, Bacillus sp.TdEND26, Bacillus subtilis strain BPA28 and Bacillus subtilis BAB-881. The maximum amylase (61.33 ± 2.14 U/ml) and protease (56.91 ± 0.23 U/ml) production were observed in Bacillus sp. TdEND26 rd. In case of co-production, the highest amount of amylase (54.13 ± 1.23 U/ml) protease (81.80 ± 4.54 U/ml) production was observed in Bacillus sp. TdEND26 at 24 hrs. Plant Tissue Cult. & Biotech. 32(1): 31-41, 2022 (June)